The postprandial serum: a neglected “tool” for nutritional studies - Piacenza, Francesco; Malavolta, Marco; Costarelli, Laura; Giacconi, Robertina; Basso, Andrea; Mocchegiani, Eugenio (Progress in Nutrition, 2014)
Studies “in vitro” designed to highlight the properties and mechanisms of action of macro- and micronutrients in cellular models are particularly important to achieve knowledge in relatively short time and with reduced costs compared to studies “in vivo”. However, the real exposure of our cells during supplementation with micronutrients may be far beyond the doses and the forms of the micronutrients used in the experiments “in vitro”. To overcome this problem, “in vitro” treatments of cell lines using serum obtained from subjects under particular dietary interventions (i.e. caloric restriction) was attempted with success. However, large part of our life occur in the post-prandial status and the postprandial serum is enriched of the various components of the diet transformed by multitude physiological processes. Hence, in this brief review we will examine the potential and will propose as tool for nutritional studies a cellular models based on treatments with the post prandial serum in order to study the effects of particular dietary intervention or supplementation with micronutrients.